RULE BREAKING DALAM PENYIDIKAN UNTUK MENGHINDARI KEKERASAN YANG DILAKUKAN OLEH PENYIDIK - Raharjo, Agus; Angkasa, Angkasa; Nugroho, Hibnu (Jurnal Dinamika Hukum, 2013)
Violence in the investigation of the suspects are still frequently performed by the investigator. This study aimed to explore the roots of violence committed by the investigator, the legal basis of the work of investigators and legal protections for suspects, and the use of a scientific investigation in the investigation. This research is a qualitative approach is normative and legal study of the law in action, is a social science that studies non-doctrinal and empirical. The results show several things. First, the investigation of violent behavior against the suspect can be found from the history of the police force who works relating to the police. Second, the investigator and the suspect had an investigation on the basis of legitimacy of national legislation and international. Third, does the rule breaking is possible in the investigation to face the deadlock in the investigation due to the behavior of suspects who do not want to give his testimony by using hypnotic techniques. Keywords: violence, investigation, suspect, rule breaking, hypnosis